OSTEOTOMIA SEGMENTAR DE MAXILA CASO CLÍNICO - Margoni Neto, Octavio (2012)
Segmental osteotomy of Maxilla Osteotomy Le Fort I or Segmented is a procedure that has become increasingly common for dentofacial deformities surgeries, known as Orthognathic Surgery. This procedure is very well indicated for the correction of discrepancies in the different plans and jaw in a single surgical time, optimizing the time of the processing treatment for which the patient is submitted. Transversal skeletal stability and the occlusal of patients, who are subjected to this type of osteotomy, has been studied in the literature, as well as, potential risks and complications associated with this procedure, the dental tissues, oro-nasal fistula, tooth loss, necrosis of some segment of the jaw or even across the jaw. The aim of this study is to present the clinical case of a patient underwent to segmental maxillary osteotomy, and to do a review of literature covering the past 10 years, with articles that discuss the stability of this procedure, as well as the potential risks and complications . Using a few key words in the electronic data base PUBMED, 12 articles were selected for this work, during the period from 2002 to 2012. Segmental osteotomy of the maxilla is a stable and safe procedure, with low complication rate, when given correctly and with the proper care in pre, trans and post-operatory.